"Prohibition to Close to Zina" Da’wa Message on @Bagasmaulanasakti Instagram Account - Sattar, Abdullah; Puspitarani, Mei; Ilaihi, Wahyu (Proceedings of International Conference on Da'wa and Communication, 2020)
This research was conducted to find out how Bagas Maulana Sakti in framing propaganda messages about the prohibition of approaching adultery through videos uploaded to his Instagram account. This research is a descriptive qualitative research using Robert N. Entman's model of framing media text analysis research which has four dimensions of analysis namely define problem, diagnose causes, make moral judgment, and treatment recommendations. Based on the analysis of the data obtained by the results of research that is in framing propaganda messages about the prohibition of approaching adultery in a video uploaded to the Instagram account @bagasmaulanasakti, Bagas Maulana Sakti is influenced by sociological and cultural aspects, where the two aspects are related in the process of selecting issues and highlighting certain aspects. The prominence can be interpreted as an effort to present the public about a certain view, that Bagas Maulana Sakti is very much against the act of promiscuity and with the video he has the aim to provide awareness or appeal to young children so as not to fall into promiscuity or adultery behavior. Recommendations for further research, researchers can use the theory of cyber media or mass media and other propaganda theories to see the extent of propaganda development in the current era of technological development.